2015
DOI: 10.17305/bjbms.2015.299
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipid dysregulation and vascular risk factors in glaucomatous retrobulbar circulation

Abstract: The aim of this study was to evaluate selected lipid-related and vascular factors and their effect on retrobulbar hemodynamics in glaucoma. Fifty-six patients with primary open angle glaucoma (POAG) [POAG group; mean age 68.32 years (SD±0.21)] and 54 patients in control group [CG, mean age 68.1 years (SD±5.34)] were examined. Peak systolic velocity, end-diastolic velocity, mean velocity, pulsatility index, and resistive index of the ophthalmic artery, the central retinal artery and the posterior ciliary arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…Causative treatment relies on a detailed understanding of the aetiology of diseases and the causes of disorders leading to their development. It has been demonstrated that age-related hemodynamic and vascular changes in retrobulbar vessels may induce pathological processes leading to ocular diseases potentially associated with significant visual impairment or irreversible blindness [1,2]. This hypothesis seems to be confirmed by the increased prevalence of many ocular diseases, in particular, glaucoma, age-related macular degeneration (AMD), and thromboembolic changes in retinal vasculature in older age groups.…”
Section: Introductionmentioning
confidence: 98%
“…Causative treatment relies on a detailed understanding of the aetiology of diseases and the causes of disorders leading to their development. It has been demonstrated that age-related hemodynamic and vascular changes in retrobulbar vessels may induce pathological processes leading to ocular diseases potentially associated with significant visual impairment or irreversible blindness [1,2]. This hypothesis seems to be confirmed by the increased prevalence of many ocular diseases, in particular, glaucoma, age-related macular degeneration (AMD), and thromboembolic changes in retinal vasculature in older age groups.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, Tang et al ( 18 ) showed that TRIG were higher, and was an independent risk factor for POAG. Other studies have also confirmed the association between LDL-C and glaucoma ( 9 , 19 ). Yilmaz et al ( 9 ) also found increased TRIG and CHOL levels in normal intraocular pressure glaucoma.…”
Section: Discussionmentioning
confidence: 53%
“…Having presumed glaucoma a vascular disorder, one should investigate the role of dyslipidemia in its etiopathogenesis. Indeed, there is research showing increased levels of TC, TG and LDL, and decreased HDL in POAG and NTG patients [35][36][37]. Furthermore, one population analysis has linked dyslipidemia with increased IOP in people not receiving glaucoma treatment, suggesting that hyperlipidemia may play a role in the onset of glaucoma [38].…”
Section: Discussionmentioning
confidence: 99%